Contrasting patterns of transposable element and satellite distribution on sex chromosomes (XY1Y2) in the dioecious plant Rumex acetosa - Steflova, Pavlina; Tokan, Viktor; Vogel, Ivan; Lexa, Matej; Macas, Jiri; Novak, Petr; Hobza, Roman; Vyskot, Boris; Kejnovsky, Eduard (Genome biology and evolution, 2013)
Rumex acetosa is a dioecious plant with the XY1Y2 sex chromosome system. Both Y chromosomes are heterochromatic and are thought to be degenerated. We performed low-pass 454 sequencing and similarity-based clustering of male and female genomic 454 reads to identify and characterize major groups of R. acetosa repetitive DNA. We found that Copia and Gypsy retrotransposons dominated, followed by DNA transposons and nonlong terminal repeat retrotransposons. CRM and Tat/Ogre retrotransposons dominated the Gypsy superfamily, whereas Maximus/Sireviruses were most abundant among Copia retrotransposons. Only one Gypsy subfamily had accumulated on Y1 and Y2 chromosomes, whereas many retrotransposons were ubiquitous on autosomes and the X chromosome, but absent on Y1 and Y2 chromosomes, and others were depleted from the X chromosome. One group of CRM Gypsy was specifically localized to centromeres. We also found that majority of previously described satellites (RAYSI, RAYSII, RAYSIII, and RAE180) are accumulated on the Y chromosomes where we identified Y chromosome-specific variant of RAE180. We discovered two novel satellites-RA160 satellite dominating on the X chromosome and RA690 localized mostly on the Y1 chromosome. The expression pattern obtained from Illumina RNA sequencing showed that the expression of transposable elements is similar in leaves of both sexes and that satellites are also expressed. Contrasting patterns of transposable elements (TEs) and satellite localization on sex chromosomes in R. acetosa, where not only accumulation but also depletion of repetitive DNA was observed, suggest that a plethora of evolutionary processes can shape sex chromosomes.
Keywords: Evolution, Molecular; molekulární evoluce; molekulární sekvence - údaje; retroelementy; chromozomy rostlin; sekvence nukleotidů; pohlavní chromozomy; Base Sequence; Molecular Sequence Data; Phylogeny; Sex Chromosomes; Chromosomes, Plant; fylogeneze; Retroelements; DNA, Satellite; satelitní DNA; Rumex